Social Science, Philosophy and Education - Barrow, Robin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2019)
This essay argues for the urgent need for philosophy as the necessary first step in any educational undertaking. Philosophy is involved with making fine distinctions which are necessary to clarify concepts and terms. The paper focuses primarily on the problems with an overreliance on scientific research in the social sciences, with special emphasis on the dangers posed in educational research. Three specific problems are identified. First, the emphasis on scientific research downgrades non-scientific research, which may be more appropriate as modes of inquiry in many aspects of education. Second, the emphasis on scientific research distorts research in areas such as the arts and humanities because individual success as a scholar is largely measured by criteria that make sense in the natural sciences but not necessarily in the arts. Third, and most significantly, the paper questions whether social action and interaction can be investigated in a truly scientific manner.